2019
DOI: 10.1051/itmconf/20192401004
|View full text |Cite
|
Sign up to set email alerts
|

Linear Bearing Fault Detection in Operational Condition Using Artificial Neural Network

Abstract: Nowadays, Factors of a competition of Hard Disk Drive (HDD) industry have reduced the cost of manufacturing process via increasing the rate of productivity and reliability of the automation machine. This paper aims to increase the efficacy of Condition-Based Maintenance (CBM) of linear bearing in Auto Core Adhesion Mounting machine (ACAM). The linear bearing faults considered in three causes such as healthy bearing, one ball bearing damage and one ball bearing damage with starved lubricant. The Fast Fourier Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition, artificial intelligence algorithms, such as genetic algorithms, fuzzy theorems, and artificial neural networks (ANNs) are employed to develop a predictive model for the fault detection of rotary mechanisms with bearing components [22][23][24][25]. Samanta et al [23] identified the fault conditions of rolling bearings based on the vibration features by using artificial neural networks with different architectures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, artificial intelligence algorithms, such as genetic algorithms, fuzzy theorems, and artificial neural networks (ANNs) are employed to develop a predictive model for the fault detection of rotary mechanisms with bearing components [22][23][24][25]. Samanta et al [23] identified the fault conditions of rolling bearings based on the vibration features by using artificial neural networks with different architectures.…”
Section: Introductionmentioning
confidence: 99%